A Wakening The Leader Within You: A Review On Leadership - Dr. Sr. Lalitha Rosali (Educational Administration: Theory and Practice, 2024)
Educational institutions and global business today call for every member of the organization to be a leader. Are leaders born or made? Whether one was born with the “special sauce” or not, if one wants to be a leader, they have to work to develop and refine the characteristics of the greats. What are you doing to awaken the leader in you? I started to reflect on it, write it down, and practice. Supposedly, every one of us is gifted, yet we need talents to develop. Now is the time to develop them. Awakening a leader in all of us is a creative method of realizing one’s leadership capabilities. This paper positively enhances self-esteem and embraces the belief that it is absolutely possible to cultivate the characteristics and skills necessary to call yourself a leader.